2014
DOI: 10.1055/s-0034-1373844
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Early Antibiotic Use and Bronchopulmonary Dysplasia in Very Low Birth Weight Infants

Abstract: Antibiotic duration > 48 hours in the 1st week of life was associated with subsequent BPD and the presence of resistant bacteria in routine ETT cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 10 publications
2
37
1
1
Order By: Relevance
“…Approximately half of these infants received a $7-day course of antibiotics with no antepartum historical risk factors or neonatal clinical signs to explain such a prolonged administration. 19 Novitsky et al 20 reported that only 18% (159 of 960) of VLBW infants received .48 hours of antibiotics during the first week of life, which was substantially lower than what we reported in this study.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Approximately half of these infants received a $7-day course of antibiotics with no antepartum historical risk factors or neonatal clinical signs to explain such a prolonged administration. 19 Novitsky et al 20 reported that only 18% (159 of 960) of VLBW infants received .48 hours of antibiotics during the first week of life, which was substantially lower than what we reported in this study.…”
Section: Discussioncontrasting
confidence: 85%
“…Antibiotic duration .48 hours in the first week after birth was associated with subsequent CLD (31% vs 14%; P , .01) and the presence of resistant bacteria in routine endotracheal aspirate cultures (7% vs 2%; P , .01) in 906 VLBW infants. 20 Cantey et al 21 reported that each additional day of antibiotic therapy in the first 2 weeks after birth was associated with both increased risk and severity of bronchopulmonary dysplasia in 1324 VLBW infants. Prolonged initial empirical antibiotic treatment $5 days with sterile blood cultures was associated with increased odds of NEC and/or death in ELBW infants (n = 5963).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, chorioamnionitis, transplacental infection, or abnormal colonization appear to be able to create an inflammatory process, first step in the pathogenesis of BPD (83). Exposure to prenatal and postnatal antibiotics, respiratory support devices, sepsis, feeding and nutrition, concurrent development of the intestinal microbiome, and the surrounding environmental microbiome, can also be also implicated (82,84,85).…”
Section: The Preterm Lung Microbiota and Bpdmentioning
confidence: 99%
“…Recently, a strong correlation was found between decreased diversity of the lung microbiome at the time of birth in preterm infants and the development of BPD (149, 152). Other studies correlated prolonged antibiotics use during the first week of life and BPD (153, 154). The protective effect of bacterial exposure in early life on asthma and allergy development, the “hygiene hypothesis,” is extensively studied, and a greater microbial diversity of commensal bacteria seems to underlie this protective effect (148).…”
Section: Current Understanding Of Bpd Pathophysiology New Pathophysimentioning
confidence: 96%